Using remote sensing and geographical information systems to classify local landforms using a pattern recognition approach for improved soil mapping - Atkinson, Jonathan Tom (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhDAgric)--Stellenbosch University, 2022.